Information Systems Design and Intelligent Applications Proceedings of Third International Conference INDIA 2016, Volume 3 - Satapathy, Suresh Chandra; Mandal, Jyotsna Kumar; Udgata, Siba K.; Bhateja, Vikrant; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2016)
The third international conference on INformation Systems Design and Intelligent Applications (INDIA - 2016) held in Visakhapatnam, India during January 8-9, 2016. The book covers all aspects of information system design, computer science and technology, general sciences, and educational research. Upon a double blind review process, a number of high quality papers are selected and collected in the book, which is composed of three different volumes, and covers a variety of topics, including natural language processing, artificial intelligence, security and privacy, communications, wireless and sensor networks, microelectronics, circuit and systems, machine learning, soft computing, mobile computing and applications, cloud computing, software engineering, graphics and image processing, rural engineering, e-commerce, e-governance, business computing, molecular computing, nano-computing, chemical computing, intelligent computing for GIS and remote sensing, bio-informatics and bio-computing. These fields are not only limited to computer researchers but also include mathematics, chemistry, biology, bio-chemistry, engineering, statistics, and all others in which computer techniques may assist.
Chapter 1. A New Private Security Policy Approach for DDoS Attack Defense in NGNs -- Chapter 2. An Effective Approach for Providing Diverse and Serendipitous Recommendations -- Chapter 3. Envelope Fluctuation Reduction for WiMAX MIMO-OFDM Signals Using Adaptive Network Fuzzy Inference Systems -- Chapter 4. Modeling and Performance Analysis of Free Space Quantum Key Distribution -- Chapter 5. Design of a Low-delay-write Model of a TMCAM -- m]Chapter 6. SLA Based E-Learning Service Provisioning in Cloud -- Chapter 7. Estimating the Similarities of G7 Countries Using Economic Parameters -- Chapter 8. Offline Malayalam Character Recognition: A Comparative Study Using Multiple Classifier Combination Techniques -- Chapter 9. A Comparative Study on Load Balancing Algorithms for SIP servers -- Chapter 10. Design of Wireless Sensor Network Based Embedded Systems for Aquaculture Environment Monitoring -- Chapter 11. Touch-to-learn: A Tangible Learning System for Hard-of Hearing Children -- Chapter 12. Creating Low Cost Multi-gesture Device Control by Using Depth Sensing -- Chapter 13. Evaluation of Glomerular Filtration Rate by Single Frame Method applying GATES Formula -- Chapter 14. Design and Development of Cost Effective Wearable Glove for Automotive Industry -- Chapter 15. Tampering Localization in Digital Image Using First Two Digit Probability Features -- Chapter 16. Classification of Bank Direct Marketing Data Using Subsets of Training Data -- Chapter 17. Offline Writer Identification and Verification - A State-of-the-Art -- Chapter 18. Handwritten Oriya Digit Recognition Using Maximum Common Sub-graph Based Similarity Measures -- Chapter 19. Design of Non-volatile SRAM Cell Using Memristor -- Chapter 20. Evolutionary Algorithm Based LFC of Single Area Thermal Power System with Different Steam Configurations and Nonlinearity -- Chapter 21. Game Theory and Its Applications in Machine Learning -- Chapter 22. A Study on Speech Processing -- Chapter 23. Forest Type Classification: A Hybrid NN-GA Model Based Approach -- Chapter 24. Optimizing Technique to Improve the Speed of Data throughput through Pipeline -- Chapter 25. An Improved Data Hiding Scheme in Motion Vectors of Video Streams -- Chapter 26. Hiding Sensitive Items Using Pearson's Correlation Coefficient Weighing Mechanism -- Chapter 27. OpenCV Based Implementation of Zhang-Suen Thinning Algorithm Using Java for Arabic Text Recognition -- Chapter 28. Numerical Modeling of Twin Band MIMO Antenna -- Chapter 29. Performance Evaluation of Video-based Face Recognition Approaches for Online Video Contextual Advertisement User-oriented System -- Chapter 30. A Survey on Power Gating Techniques in Low Power VLSI Design -- Chapter 31. Phase Based Mel Frequency Cepstral Coefficients for Speaker Identification -- <Chapter 32. A New Block Least Mean Square Algorithm for Improved Active Noise Cancellation -- Chapter 33. An Improved Feedback Filtered-X NLMS Algorithm for Noise Cancellation -- Chapter 34. Application of Internet of Things (IoT) for Smart Process Manufacturing in Indian Packaging Industry -- Chapter 35. Function Optimization Using Robust Simulated Annealing -- Chapter 36. Analysis and Optimization of Feature Extraction Techniques for Content Based Image Retrieval -- Chapter 37. Parametric Curve Based Human Gait Recognition -- Chapter 38. An Energy Efficient Proposed Framework for Time Synchronization Problem of Wireless Sensor Network -- Chapter 39. Epigenetic and Hybrid Intelligence in Mining Patterns -- Chapter 40. A Technical Review on LVRT of DFIG Systems -- Chapter 41. An AIS Based Approach for Extraction of PV Module Parameters -- Chapter 42. Word Sense Disambiguation in Bengali: An Auto-updated Learning Set Increases the Accuracy of the Result -- Chapter 43. Efficient Methods to Generate Inverted Indexes for IR -- Chapter 44. Intelligent Mail Box -- Chapter 45. Learning Based No Reference Algorithm for Dropped Frame Identification in Uncompressed Video -- Chapter 46. Multi-view Video Summarization -- Chapter 47. Comprehensive Review of Video Enhancement Algorithms for Low Lighting Conditions -- Chapter 48. A Detailed Review of Color Image Contrast Enhancement Techniques for Real Time Applications -- Chapter 49. A Conceptual Model for Acquisition of Morphological Features of Highly Agglutinative Tamil Language Using Unsupervised Approach -- Chapter 50. A Fuzzy Approach for the Maintainability Assessment of Aspect Oriented Systems -- Chapter 51. Split and Merge Multi-scale Retinex Enhancement of Magnetic Resonance Medical Images -- Chapter 52. Review on Secured Medical Image Processing -- Chapter 53. Identification of Stages of Malignant Tumor in MRM Images using Level Set algorithm and Textural Analysis -- Chapter 54. Reviews Based Mobile Application Development Model (RBMAD) -- Chapter 55. Three Phase Security System for Vehicles Using Face Recognition on Distributed Systems -- Chapter 56. SLA Based Utility Analysis for Improving QoS in Cloud Computing -- Chapter 57. A Descriptive Study on Resource Provisioning Approaches in Cloud Computing Environment -- Chapter 58. Analyzing the Performance of a Software and IT Growth with Special Reference to India -- Chapter 59. Stock Price Forecasting Using ANN Method -- Chapter 60. Recognition of Handwritten English Text Using Energy Minimisation -- Chapter 61. A Novel Codification Technique for Tacit Knowledge in Software Industry Using Data Mining techniques -- Chapter 62. An Analysis on the Effect of Malicious Nodes on the Performance of LAR Protocol in MANETs -- Chapter 63. Qualitative Performance Analysis of Punjabi and Hindi Websites of Academic Domain: A Case Study -- Chapter 64. A Robust, Privacy Preserving Secret Data Concealing Embedding Technique into Encrypted Video Stream -- Chapter 65. Trusted Execution Environment for Data Protection in Cloud.
Keywords: Computational intelligence; Signal processing; Artificial intelligence; Computational Intelligence; Signal, Speech and Image Processing; Artificial Intelligence